Parkin- and PINK1-Dependent Mitophagy in Neurons: Will the Real Pathway Please Stand Up? - Grenier, Karl; McLelland, Gian-Luca; Fon, Edward A. (Frontiers in Neurology, 2013)
Parkinson’s disease (PD) is characterized by massive degeneration of dopaminergic neurons in the substantia nigra. Whereas the majority of PD cases are sporadic, about 5 to 10 percent of cases are familial and associated with genetic factors. The loss of parkin or PINK1, two such factors, leads to an early-onset form of PD. Importantly, recent studies have shown that parkin functions downstream of PINK1 in a common genetic pathway affecting mitochondrial homeostasis. More precisely, parkin has been shown to mediate the autophagy of damaged mitochondria (mitophagy) in a PINK1-dependent manner. However, much of the work characterizing this pathway has been carried out in immortalized cell lines overexpressing high levels of parkin. In contrast, whether or how endogenous parkin and PINK1 contribute to mitophagy in neurons is much less clear. Here we review recent work addressing the role of parkin/PINK1-dependent mitophagy in neurons. Clearly, it appears that mitophagy pathways differ spatially and kinetically in neurons and immortalized cells, and therefore might diverge in their ultimate outcome and function. While evidence suggests that parkin can translocate to mitochondria in neurons, the function and mechanism of mitophagy downstream of parkin recruitment in neurons remains to be clarified. Moreover, it is noteworthy that most work has focused on the downstream signaling events in parkin/PINK1 mitophagy, whereas the upstream signaling pathways remain comparatively poorly characterized. Identifying the upstream signaling mechanisms that trigger parkin/PINK1 mitophagy will help to explain the nature of the insults affecting mitochondrial function in PD, and a better understanding of these pathways in neurons will be the key in identifying new therapeutic targets in PD.